2003
DOI: 10.1021/ja0282691
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-Confined Nano-RuO2:  A Green, Selective, and Efficient Catalyst for Aerobic Alcohol Oxidation

Abstract: The development of green, selective, and efficient catalysts, which can aerobically oxidize a variety of alcohols to their corresponding aldehydes and ketones, is of both economic and environmental significance. We report here the synthesis of a novel aerobic oxidation catalyst, a zeolite-confined nanometer-sized RuO(2) (RuO(2)-FAU), by a one-step hydrothermal method. Using the spatial constraints of the rigid zeolitic framework, we sucessfully incorporated RuO(2) nanoparticles (1.3 +/- 0.2 nm) into the superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
196
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(206 citation statements)
references
References 49 publications
9
196
0
1
Order By: Relevance
“…It can be concluded that the Ru ions in the two materials have the same Ru(IV) oxidation state. These data compare well with those reported for related Ru(IV) systems (18). Instead, the main absorption edge of Ru(III)POM is shifted to lower photon energies (by 2 eV), which is consistent with a lower oxidation state of Ru.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It can be concluded that the Ru ions in the two materials have the same Ru(IV) oxidation state. These data compare well with those reported for related Ru(IV) systems (18). Instead, the main absorption edge of Ru(III)POM is shifted to lower photon energies (by 2 eV), which is consistent with a lower oxidation state of Ru.…”
Section: Resultssupporting
confidence: 90%
“…The Ru(IV)POM and hydrous RuO 2 display identical XANES edge and line shape. The edge position is known to depend on the ruthenium oxidation state, shifting to higher photon energy as the valence state increases (17,18). It can be concluded that the Ru ions in the two materials have the same Ru(IV) oxidation state.…”
Section: Resultsmentioning
confidence: 99%
“…The results in this work apply well to real Ru catalyst systems, which are nano-particles forming amorphous oxide with not well-defined stoichiometry [34,35]. Such 'oxidized' states of the Ru nanoparticles, often described as Ru x O y , are comparable to the 'surface oxide' with subsurface oxygen rather than with the well-structured RuO 2 (110) surface.…”
Section: Discussionsupporting
confidence: 57%
“…[11][12][13][14][15] In this work, Ru/Al 2 O 3 was chosen as it is commercially available at a reasonable cost, thus accessible to most synthetic laboratories.…”
Section: Choice Of Catalystmentioning
confidence: 99%